2020
DOI: 10.1055/s-0040-1714299
|View full text |Cite
|
Sign up to set email alerts
|

Computed Tomography Enhances Diagnostic Accuracy in Challenging Medial Coronoid Disease Cases: An Imaging Study in Dog Breeding Appeal Cases

Abstract: Objectives The aim of this study was to determine the radiographic sensitivity in detecting medial coronoid disease (MCD), using computed tomography (CT) as reference in dogs presented for an official second opinion, and to compare the medial coronoid process (MCP) in fragmented and fissured MCP as well as those unaffected by MCD. Materials and Methods The data of dogs, presented for official second opinion radiographs and CT, were reviewed by three board-certified observers and in accordance with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…33 Accordingly, under normal physiologic conditions, reduction in BMD and therefore attenuation may reflect altered load within the osseous structures of the elbow joint. Phillips et al 6 postulate a caudolateral load transfer within affected thoracic limbs as the physiologic mechanism underlying the reduction in overall attenuation of the MCP in dogs with MCD, a theory supported by the results of our study and the findings of the recent work by Wennemuth et al 34 We additionally found a parallel reduction in attenuation within the PRC, a finding supported by that of Villamonte-Chevalier et al 28 in their population of Golden and Labrador Retrievers. This finding might further support the theory proposed by Phillips et al, 6 given the roughly equal load sharing of the radius and ulna reported with in vitro force plate analysis in the canine elbow joint by Mason et al 35 A caudolateral load shift through the ulna could reasonably be expected also to unload the radius to a degree significant enough to result in reduced BMD.…”
Section: Discussionsupporting
confidence: 90%
“…33 Accordingly, under normal physiologic conditions, reduction in BMD and therefore attenuation may reflect altered load within the osseous structures of the elbow joint. Phillips et al 6 postulate a caudolateral load transfer within affected thoracic limbs as the physiologic mechanism underlying the reduction in overall attenuation of the MCP in dogs with MCD, a theory supported by the results of our study and the findings of the recent work by Wennemuth et al 34 We additionally found a parallel reduction in attenuation within the PRC, a finding supported by that of Villamonte-Chevalier et al 28 in their population of Golden and Labrador Retrievers. This finding might further support the theory proposed by Phillips et al, 6 given the roughly equal load sharing of the radius and ulna reported with in vitro force plate analysis in the canine elbow joint by Mason et al 35 A caudolateral load shift through the ulna could reasonably be expected also to unload the radius to a degree significant enough to result in reduced BMD.…”
Section: Discussionsupporting
confidence: 90%
“…ED includes medial coronoid process disease (MCPD), osteochondrosis/osteochondritis dissecans (OC/OCD) of the humeral trochlea, ununited anconeal process (UAP) and joint incongruence (INC). These conditions can occur alone, or in association with each other [1][2][3][4][5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…This contrasts with prior literature which compares a population of dogs of a variety of breeds affected by elbow dysplasia with sound dogs of a mixed population. 18,20,21 Our data suggest that sclerosis in these regions may represent a breed or population variation and not necessarily an association with elbow dysplasia. Internationally, Guide Dog organizations endeavour to reduce disease within their populations and the use of CT to screen for the presence of elbow dysplasia is being increasingly utilized.…”
Section: Discussionmentioning
confidence: 70%
“…Phillips and colleagues 19 used a linear scale to measure 5% increments of the entire ulna and demonstrated decreased BMD at the MCP apex and increased BMD in the base of the MCP in dogs with MCPD. Wennemuth and colleagues 21 measured the tip of the MCP and displayed decreased BMD in dogs with FMCP. Humphreys and colleagues 22 measured the apex of the MCP to the level of the The purpose of our publication was not to identify regions associated with disease, but develop an overall estimate of sclerosis of the MCP and humeral trochlea and compare if breed variations exist.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation